A Biologically Compatible Colorimetric Sensor for the Selective Recognition of Cu2+ Ions in Biological Matrices. Issue 45 (5th December 2022) - Fazal, Mahmood; Ali, Imdad; Ahmed, Farid; Khalid, Shumaila; Farghaly, Thoraya A.; Althagafi, Ismail I.; Khan, Irfan; Ali, Mumtaz; Ateeq, Muhammad; Shah, Muhammad Raza
Abstract: Heavy metal ions pollution is posing a major danger to human health across the planet. We present a phenylhydrazone‐based colorimetric sensor for detecting Cu 2+ ions in tap water and human blood plasma. The phenylhydrazone‐based sensor (Sensor 1 ) is extremely selective for recognizing Cu 2+ ions over other similar metal ions by producing a colorimetric response. Upon interaction with Cu 2+, the colorless sensor 1 changes to dark yellow within a minute producing a bathochromic shift in the absorption spectrum. The AFM, Zetasizer and FTIR spectroscopic techniques were used for Cu 2+ detection and selectivity of sensor 1 . The average size of sensor 1 is around 293.9 nm which changes to 2275 nm upon complexation with Cu 2+ . Sensor 1 was highly selective towards Cu 2+ as no interference was recorded by various metals ions. The detection limit was found to be 0.1  μ M with R 2 equal to 0.9821. Furthermore, cytotoxic experiments showed that sensor 1 is nontoxic to various cell lines, which revealed that it could detect Cu 2+ ions in the biological system. Moreover, sensor 1 gives satisfactory results for detecting Cu 2+ ions in human blood plasma and real water samples. Abstract : A phenylhydrazone‐based colorimetric sensor for detecting Cu 2+ ions in tap water and human blood plasma is developed. The sensor is extremely selective for recognizing Cu 2+ ions over other similar metal ions by producing a colorimetric response (changes to dark yellow within a minute). The sensor gives satisfactory results for detecting Cu 2+ ions in human blood plasma and real water samples.